2021
DOI: 10.3390/ijms221810076
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Molecular Networks in the Cerebellum in Chronic Schizophrenia: Modulation by Early Postnatal Life Stressors in Murine Models

Abstract: Despite the growing importance of the cerebellum as a region highly vulnerable to accumulating molecular errors in schizophrenia, limited information is available regarding altered molecular networks with potential therapeutic targets. To identify altered networks, we conducted one-shot liquid chromatography–tandem mass spectrometry in postmortem cerebellar cortex in schizophrenia and healthy individuals followed by bioinformatic analysis (PXD024937 identifier in ProteomeXchange repository). A total of 108 up-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 87 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Indeed, METTL7A expression levels have previously been investigated in brain tissue in schizophrenia. A recent proteomic study found a reduction in METTL7A protein levels in the cerebellar cortex in schizophrenia patients and in the schizophrenia murine models [14]. In our study, we found that the main source of METTL7A in the cerebellar cortex is in the GFAP-positive cells.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Indeed, METTL7A expression levels have previously been investigated in brain tissue in schizophrenia. A recent proteomic study found a reduction in METTL7A protein levels in the cerebellar cortex in schizophrenia patients and in the schizophrenia murine models [14]. In our study, we found that the main source of METTL7A in the cerebellar cortex is in the GFAP-positive cells.…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, Gene Ontology classifies the biological function of METTL7A in neutrophil degranulation and its subcellular localization in lipid droplets. Studies in different areas of the human brain have revealed changes in METTL7A in schizophrenia [14][15][16]. One of these studies identified a reduction in METTL7A protein levels in the cerebellar cortex in schizophrenia subjects and stress mouse models, respectively [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that the downregulation of METTL7A in tumor tissues predicted a poor prognosis in HCC patients [ 15 ], and that inhibiting METTL7A might help choriocarcinoma cells respond to methotrexate (MTX)-based chemotherapy [ 16 ]. In the context of neutrophil degranulation, changes in METTL7A expression may compromise the integrity of the Golgi apparatus, resulting in abnormal neutrophil secretory granule production and altering the first defense barrier of the innate immune response in chronic schizophrenia [ 31 ]. Another study investigated the role of METTL7A in preserving the integrity of the Golgi, which may be crucial for neutrophil degranulation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another major area affected in schizophrenia is the cerebellum [ 167 ]. Among other functions, this region is also involved in attention, working memory, verbal learning, sensory discrimination, control of motor activity, in motor learning and has a sensorimotor calibration, depending on the context in which the individual is.…”
Section: Major Regions Involved In Schizophreniamentioning
confidence: 99%